Influence of locking and passive soft switching on hydraulic circuit efficiency. (March 2017) - Mahato, Anil C; Ghoshal, Sanjoy K; Samantaray, Arun K
Throttling and fluid compressibility losses are the major losses which occur during the valve transition in a switched mode hydraulic circuit. To minimize the throttling energy loss, a soft switch concept with lock and release mechanism was introduced by different researchers. In the literature, two different kinds of soft switches, one locking and another passive, were introduced in a hydraulic circuit. Thereafter, experimental validation was reported considering only a locking-type soft switch. But the influence of the passive soft switch on the performance of the hydraulic system was not reported. In this article, how the passive soft switch would affect the system efficiency has been investigated through bond graph model simulation. It has been shown both numerically and experimentally by other researchers that the use of a passive soft switch and a locking mechanism, depending upon configuration, can lead to more than 66.1% reduction in throttling energy loss. In this article, it has been further shown that an additional 3.25% throttling energy is saved when the passive soft switch is discarded from the system and only the locking mechanism is retained. The critical parameters of the locking soft switch have been optimized through multi-run simulation and, thereafter, a relationship between the critical parameters of the locking soft switch and the throttling energy loss of the valve has been obtained by using multiple regression analysis. Also, the variations of energy losses with respect to different valve orifice areas, duty cycles, and pulse width modulation frequencies are investigated through simulation.